Changes of Antimicrobial Resistance Causing Infections Following Transrectal Prostate Biopsy: Analysis of 10-Year Data - Da Eun Han; Sun Tae Ahn; Jong Wook Kim; Du Geon Moon; Hong Seok Park; Mi Mi Oh (Urogenital Tract Infection)
Purpose The production of extended-spectrum b-lactamases (ESBLs) has emerged as one of the main causes of antimicrobial resistance. It is well known that infections of ESBL-producing Enterobacteriaceae causes poor clinical outcomes. This study investigated the changes in the antimicrobial resistance patterns in infections following transrectal ultrasound-guided prostate (TR) biopsy over a 10 year period and analyzed whether the clinical course varies in infections caused by the ESBL-producing Enterobacteriaceae. Materials and Methods We retrospectively analyzed patients who had infections after a TR biopsy at the Korea University Guro Hospital from January 2010 to October 2019. Infection from a TR biopsy was defined as readmission due to a fever of 38 degrees or higher that occurred within one week after the biopsy. Results Among 1,855 patients who received a TR biopsy, 39 patients (2.10%) had infectious complications. Of 33 culture-positive patients, 29 patients (87.9%) showed quinolone resistance, 10 patients (30.3%) were ESBL-positive and 9 patients had concomitant quinolone resistance and were also ESBL-positive. 75% of ESBL-positive bacterial infections occurred after 2016 indicating increasing incidence in recent days. The only significant difference in the clinical course between the ESBL-negative and the positive group was the lower systolic blood pressure of the ESBL-positive group during hospitalization (p-value=0.018). Conclusions Infections due to the ESBL-producing Enterobacteriaceae showed a tendency to increase among TR biopsy patients since 2016. Although the clinical course of the ESBL-positive infection did not show significant differences to ESBL-negative infection, further analysis is needed because of the small number of patients.